The Estimation of Fracture Intensity and Pressure Distribution using Analysis of Shear Wave Splitting on “Landak” Geothermal Field - Muhammad Al Thariqsyah; Irvan Ramadhan; Sudarmaji Sudarmaji (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Shear wave splitting is a study that utilizes the differences between arrival times of two shear waves (slow and fast) propagating from a source to a receiver to identify the magnitude of the anisotropic medium through which they propagate. Aside from generating a delay time between two shear waves, the anisotropic medium also shifts the polarization of fast shear wave from its initial polarization which is indicated as the main orientation of the related fracture system. The study was conducted on Landak Field, located around Bukit Besar mountain range by analyzing provided data from December 2011 to April 2012. The results of this study show that the polarizations of fast shear waves in several stations are as following; NE-SW orientation at station R09, R17, R25, and R26, N-S orientation at station R08, and NW-SE orientation at station R17. Not only do these orientations of polarization show a good correlation with structural analysis in this area, but also important to be noted that all microseismic stations encounter a wide-spreading polarization phenomenon as an effect of complex anisotropy. The delay time from all stations ranges from  0.03 to 0.07 seconds. The normalization between delay time and length of ray path for all stations results in a fracture intensity parameter ranging from 0.004 to 0.011 seconds/km. This intensity is measured in slowness parameters, which shows increased value towards the Bukit Besar area, which potentially becomes the upflow zone of the geothermal system. The study shows that the distribution of fracture intensity and pressure have correlation and identical trend with temperature distribution.